KORUPSI DAN PEMBANGUNAN PENDIDIKAN DI INDONESIA - Titik Handayani (Research Centre for Population, Indonesian Institute of Sciences, 2009)
The right of education for all, in Indonesia has been mandated in some articles of the Indonesian constitutions. To fulfill this mandate, the Indonesian government emphasis that 20% budget have to be allocated for the development of education. Through those high budgets, education in Indonesia is expected to increase its quality. But that goal has not been achieved as fully as expected. Some people, especially which came from poor family and isolated area, still having the obstacles of education accessibility. The budget leaking the education sector, influence the quality of education services for poor people. The aim of this article is to discuss the problems of education development achievement and the implication of corruptions in education sector In reality, the institutions of education are facing many corruption problems, but actually this institution is a strategic media to internalization values of anticorruption to fight against the corruption. Students which will become the successor of this country should be taught and forced to have a nerve to fight against the corruption. For those reasons above, the education's substances of anticorruption need to be given for students earlier. Moreover, the improvement of governance in education sector need to be done, through opening the public's participation to encourage the transparency and accountability ofbudget control, and also formulate the education policy in order to avoid the misappropriation of education budget.Keywords : Development of education, corruption and regional autonomy